Analisis Faktor-Faktor yang Mempengaruhi Penggunaan SAK EMKM ada UMKM Dibidang Asosiasi Pengusaha Indonesia DPP Lampung - Tria Restiani; Sri Astuti; Arif Makhsun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are critical to the Indonesian economy because they provide jobs and boost the local economy. However, MSMEs continue to disregard the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). With assistance from the Lampung Provincial Leadership Council (DPP) of the Indonesian Employers Association (APINDO), this study aims to investigate the factors influencing the use of SAK EMKM in MSMEs. SAK EMKM socialization, business size, length of operation, and educational background are among the factors analyzed. Survey-based quantitative approach is used in this study. 107 MSMEs received questionnaires from APINDO DPP Lampung in order to gather primary data. Multiple linear regression analysis, validity tests, reliability tests, and traditional assumption tests were performed on the data using SPSS software. Partial tests (t-tests) and coefficients of determination were used to test hypotheses. The study's findings show that SAK EMKM use in MSMEs supported by APINDO DPP Lampung is influenced by educational background, length of operation, and socialization. Meanwhile, SAK EMKM's use is mostly unaffected by the size of the company. This finding implies that the adoption of SAK EMKM is more influenced by the socialization, business experience, and skill levels of MSME members than by the size of the firm. It is anticipated that this study would help academics and MSME participants use SAK EMKM more effectively in order to achieve sustainable MSME financial management.